Avaliação do desempenho mecânico de juntas soldadas do aço ASTM 743 CA6NM utilizado na fabricação de rotores de turbinas hidraúlicas tipo Francis - Ceron, Samuel (2016)
The ASTM 743 CA6NM steel is widely used in making components for hydraulic turbines, in particular Francis rotors. The welding process, which is used in the manufacture, is of fundamental importance in the structural reliability of the rotors, as well as in their lifetime in operation, since the welded joint must resist to all the mechanical stresses imposed on the rotors during operation. In this context, this survey was outlined through a planned study, in order to evaluate the mechanical performance of four different concepts of welded joints that can be applied in the manufacture of rotors, analyzing the microstructural changes in each study condition and correlating with the results of mechanical tests, as well as with found failure mechanisms. At the end of the work, it is concluded that the heat treatment after welding is indispensable to ensure an adequate mechanical performance of welded joints of ASTM 743 CA6NM steel by GMAW process. It is also concluded that the study condition which has used the ER309L filler metal austenitic in the root pass and the ER410NiMo martensitic action metal in the filling passes, with subsequent heat treatment, has showed the best results in the traction trials and tenacity to the impact. Thus, it is the most suitable for the application in the manufacture of turbine rotors with ASTM 743 CA6NM steel. The presence of δ ferrite with formation in the biphasic region has not affected directly the results in the impact tenacity testing, so it was required a specific study to assess the effect of the proposed conditions. In the fatigue tests, the obtained results show that the quality of the molten material can interfere significantly in the life in fatigue of conditions proposed in this study, because the ruptures occurred preferably in the failure of molten base material. It was also observed that all the samples have reached the number of minimum cycles for the severe working conditions of a Francis rotor.